Health, Human Security And The Peri-urban Transition In The Mekong Delta: Market Reform, Governance And New Analytic Frameworks For Research In Southeast Asia - H. Spencer, James (Penerbit Universiti Sains Malaysia (USM Press), 2007)
This paper identifies links between (i) the emergence of a global niche in food processing export industries such as those in Vietnam and similar regions of Southeast Asia, (ii) new forms of governance associated with these dispersed but densely settled industrial regions that result in a highly decentralized model for water service provision institutions, and (iii) some of the potentially emerging health challenges associated with such rapid peri-urbanization, changing consumption patterns, and decentralized provision of basic infrastructure. Such settlement and institutional transitions have made the job of the urban planner more complicated even as it may increase the level of threat to human and environmental security through the emergence of previously unknown diseases like avian influenza or the re-emergence of formerly controlled ones such as dengue fever.